PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN SEKSUAL BERBASIS GENDER DAN ANAK BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL DI WILAYAH KABUPATEN BANYUMAS - Utami, Pangestika Rizki (Universitas Muara Bungo, 2026)
The incidence of sexual violence is on the rise in Indonesia. In practice, victims of sexual violence frequently encounter discrimination across various domains. With the ratification of Law Number 12 of 2022 concerning Sexual Violence Crimes (SVCL), it is anticipated that victims of sexual violence will be able to secure assurances of justice and legal certainty, as well as opportunities for recovery. The purpose of this study is to analyze the implementation of the SVCL in the legal jurisdiction of Banyumas Regency. This research is categorized as field research. The method of data collection involved participant observation. The collected data was then analyzed using a series of steps including data reduction, data display, and data verification. This analysis was conducted by applying Chamblis and Seidman's theory on the operation of law within society. Based on the research findings, the Banyumas Child Protection and Empowerment Unit (UPTD PPA Banyumas) plays a pivotal role in the implementation of the SVCL concerning legal protection within the jurisdiction of Banyumas Regency. This encompasses various processes such as receiving community or victim complaints, as well as providing medical, psychological, and legal support. The legal support offered by UPTD PPA Banyumas encompasses procedures ranging from police investigations, prosecution by the attorney's office, to the evidentiary examination process in court. Another form of legal protection extended to victims is the fulfillment of restitution. Restitution fulfillment is pursued with the assistance of the Witness and Victim Protection Agency (LPSK) through the trial's evidentiary process in court. This will serve as a fundamental legal consideration for judges in rendering verdicts concerning cases of sexual violence.